Financial Control Strategies Based on Maritime Culture among theTorosiaje Community in Indonesia: A Mental Accounting Perspective - Tri Handayani Amaliah; Nilawaty Yusuf (Universitas Hayam Wuruk Perbanas, 2026)
This study investigates the financial control strategies practiced by the Torosiaje ethnic community, a maritime society in Tomini Bay, Indonesia, through the lens of mental accounting. Culturally oriented, the Torosiaje society shows that money management involves much more than purely economic aspects because it is highly social, religious, and ecological in nature. Qualitative methodology was used in this research with the help of ethnomethodology, while data were collected using in-depth interviews of lobster entrepreneurs, fishermen, traditionalists, and village authorities along with participant observations of interactions among members of the studied community. Ethnomethodologically, steps of data reduction, data presentation, indexicality, reflexivity, and conclusion making were used during the data analysis. The research findings show that money can be classified into ritual, social, and economic categories, which means that financial behavior is governed by cultural wisdom. The studied culture develops appreciation and understanding of local values of sipadakauang (unity) and sikarimanan (mutual affection), which together result in achieving balance psychologically as well as socially and ecologically. The main novelty of the present research consists in its combination of behavioral finance and maritime anthropology, thereby providing a unique insight into how mental accounting works under certain socio-cultural conditions.